Efficacy of fungicides in controlling blast disease of pearl millet - and C.J. DANGARIA, CLARA M. LUKOSE*, D.L. KADVANI (Indian Phytopathology, 2007)
Once considered a minor disease, Pearl millet blast (Pyricularia penniseti) has recently become important in many of the high yielding hybrids in certain parts of Gujarat State. Fungicides were tested to know their efficacy in controlling the disease in the field during three years, 2001, 2003 and 2004 at Millet Research Station, Jamnagar, Gujarat. Out of eight fungicides tested, carbendazim @ 0.05% was significantly superior in contrOlling the disease with the lowest disease intensity (28.3%) followed by thiophanate methyl (29.9%) and mancozeb (32.8%). There was also a significant increase in grain yield in carbendazim (2239 kg/ha) followed by thiophanate methyl (2014 kg/ha) and mancozeb (1910 kg/ha). Likewise, the fodder yield also increased significantly in carbendazim treatment (3241 kg/ha). The maximum net return of Rs. 3411/- was recorded in this treatment with highest ICBR of 1:3.85. It is thus concluded that the fungicide carbendazim 50 WP @ 0.05% should be sprayed twice for controlling the blast disease of pearl millet.